MODEL PELATIHAN WIRAUSAHA JASA BOGA BERWAWASAN GENDER BAGI REMAJA PESANTREN - Siti Malikhah Towaf (Universitas Negeri Malang, 2016)
Abstract: A Model of Training on Culinary Enterprise Imbued with Gender Perspectives for Disciples of Pesantren. Pesantrens have strategic role in character building and internalizing a holistic and Islamic personality values such as: strong faith, obedience to Syariat and splendour in Akhlaq. Pesantrens concentrate in educating youngsters through yellow books studies which contribute to gender bias among santries. This study explores gender perspectives and entrepreneurship in pesantren and developed an entrepreneurship training model in culiner with gender perspectives. A qualitative approach with developmental design is used to design a training model by creating prototype of training model, trying it out and examining it in terms of effectivity, efficiency and appealling of the model. The data were collected by review litterature, documentary study, observation, interview and handing out an open ended questionaire. Those data were analized inductivelly and comparatively to describe gender perspective and entrepreneurship; and produce an entrepreneurship training model in culiner with gender perspectives which is ready to be implemented to the youngsters in pesantren as the target groups. Abstrak: Model Pelatihan Wirausaha Jasa Boga Berwawasan Gender bagi Remaja Pesantren. Pendekatan kualitatif dengan desain pengembangan digunakan untuk merancang model pelatihan wirausaha jasa boga berwawasan gender bagi remaja pesantren, dengan membuat prototipe, menguji coba dan mencermati sisi efektivitas, efisiensi dan daya tarik model pelatihan di tiga pesantren pedesaan dengan gaya hidup yang penuh kesederhanaan, di Kabupaten Malang. Pelatihan wirausaha jasa boga berwawasan gender bagi remaja pesantren, efektif memenuhi kebutuhan santri menambah wawasan tentang gender dan wirausaha, memberi keterampilan dalam tataboga; efisien dalam penggunaan waktu, tenaga dan bahan-bahan untuk praktik tata boga; dan menarik minat peserta.